2000
DOI: 10.1017/s1350482700001614
|View full text |Cite
|
Sign up to set email alerts
|

The impact of observations on Mesoscale Model forecasts of three‐hourly rainfall accumulations

Abstract: The aim of data‐impact studies at the UK Met. Office is to investigate how observations affect the accuracy of model forecasts. Results from such experiments provide useful evidence on which to base the design of observational networks. This project, using a case study approach, investigated the relative benefit of different observation types within The Met. Office's Mesoscale Model domain on forecasts of three‐hourly precipitation accumulation over the UK up to 12 hours ahead. The method used assesses the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Increasing the frequency of the radar data assimilated from 3-hourly to hourly improves the first 6 h of the forecast. One observation impact study (Anderson, 2002) examined forecasts in which observations had given a significant improvement in 6-12 h rainfall forecasts, and investigated the origin of the improvement. Radar data were found to be the most frequent source of the benefit with a similar frequency for other data types such as aircraft and radiosonde.…”
Section: Derived Productsmentioning
confidence: 99%
“…Increasing the frequency of the radar data assimilated from 3-hourly to hourly improves the first 6 h of the forecast. One observation impact study (Anderson, 2002) examined forecasts in which observations had given a significant improvement in 6-12 h rainfall forecasts, and investigated the origin of the improvement. Radar data were found to be the most frequent source of the benefit with a similar frequency for other data types such as aircraft and radiosonde.…”
Section: Derived Productsmentioning
confidence: 99%
“…However, using a similar method of serial casestudies, radiosonde humidity profiles have been found to be very beneficial for shortrange mesoscale model forecasts of rain accumulation (e.g. Anderson et al 1998a).…”
Section: (C) Discussion Of Resultsmentioning
confidence: 99%
“…in hPa, where ρ 0 is in g/m 3 . An approximation of the saturation moist air pressure as a function of temperature profile is given as [17] ( 5 ) in hPa.…”
Section: The Forward Modelmentioning
confidence: 99%
“…In fact, produced [2] by evaporation of warm ocean water, it is redistributed vertically and horizontally across the globe by deep convective cells and large-scale eddies, influencing global circulation models forecasts. Furthermore, in a recent study [3] the moisture field resulted the most beneficial individual observation type for improving the accuracy of forecasts of precipitation accumulation from the UK Met. Office Mesoscale NWP Model.…”
Section: Introductionmentioning
confidence: 99%